Relatório de Estágio Profissional "Ode à docência: uma obra da Identidade Profissional" - Carla Sofia Valério Fernandes (2017)
Ode à docência: uma obra da identidade profissional is the document prepared by an intern student, where her supervised teaching practice is reported, revealing, rethinking and reflecting her experiences as a physical education teacher, in her last year of formation. It is directed by the trajectory played by a playwright in the creation and construction of a play, divided in eight great chapters. The first one corresponds to the Synopsis where the predominant information for the understanding of the document is enunciated. The second, corresponds to the Technical Sheet, which shows the characteristics of the playwright as the main actor in the plot, as well as the expectations revealed by him in relation to the whole process. The third fits the reader in the Scenic Space of the work, highlighting the characteristics of the context where the teaching practice occurred. The fourth clarifies the characteristics of the actors in the process, and the following chapter, corresponding to the Show, reveals how the playwright acted in the face of contextual constraints, giving life to his performance in the context of teaching. In the sixth chapter, the moments of intervention with the community are exposed, depicting specific moments of interaction with the context. The seventh chapter looks at the research-action study, portraying the perception of a intern student and her students about the process of building the professional identity of the "good" physical education teacher. To conclude, chapter eight presents the main criticisms of the show, confiding the most prominent conclusions that were expressed at the end of the entire process of building the intern student professional identity.